A cross-sectional study to determine the challenges in minimally invasive gynaecological surgeries - Prajapati, Parwati; Bhattacharjee, Somen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Minimally invasive gynaecological surgery is widely practiced, yet it is associated with specific surgical and non-surgical challenges. This cross-sectional study aimed to assess the challenges and complications encountered during minimally invasive gynaecological surgeries at a tertiary healthcare centre. Methods: A cross-sectional study was conducted from May 2022 to April 2023 at a tertiary care centre. All women undergoing laparoscopic gynaecological surgeries were included, excluding laparoscopic tubectomy and malignancy cases. Data were obtained from medical records and included age, parity, indication for surgery, intraoperative difficulties, duration of surgery, and postoperative outcomes. Results: Most patients were aged 21-40 years (57.5%), belonged to the middle socioeconomic class (70%), and were multiparous (para 2-3). Common indications included abnormal uterine bleeding (38.8%), uterine fibroids (26.3%), and ovarian cysts/endometrioma (25%). Total laparoscopic hysterectomy was the most frequently performed procedure (33.8%), followed by diagnostic hysterolaparoscopy (18.8%). The overall complication rate was 31.25%, with major complications in 11.25% and minor complications in 20% of cases. Intraoperative bleeding requiring blood transfusion occurred in 6.25% cases, organ injuries in 3.75%, and conversion to laparotomy in 5%. Technical difficulties such as equipment issues or staff unavailability were noted in 12.25% cases. Postoperative complications included fever (10%), ureteric injury (2.5%), urinary tract infection (3.75%), stress urinary incontinence (2.5%), and vaginal cuff dehiscence (1.25%). Most surgeries lasted 121-180 minutes (45%). Conclusions: Minimally invasive gynaecological surgeries are generally safe but not without risk. Higher complication rates may be related to procedural complexity and surgeon experience. Individualized patient assessment, surgical expertise, and adequate resources are essential to reduce complications.